The Effect of Applying Role Playing Model to Improve Indonesian Language Learning Outcomes Class IV SD Negeri 1 Metro Pusat - Khasbullah, Firada; Herpratiwi, Herpratiwi; Firdaus, Rangga; Khasbullah, Fizzaria (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2025)
The problem in this study is the low learning outcomes of Indonesian language in IV class students of SD Negeri 1 Metro Pusat. The purpose of this study was to determine the effect of the application of the role playing model on Indonesian learning outcomes. This study used a quasi-experimental method with the design form used was a non-equivalent control group design. The research sample amounted to 57 students. Data collection techniques using tests. Researchers collected data for 2 meetings in the experimental class and 2 times in the control class, students’ Indonesian learning outcomes were assessed from pretest and posttest questions given by researchers. The questions used were in the form of multiple choice questions as many as 10 questions. The results showed that there was an influence in the application of the role playing model on Indonesian language learning outcomes in class IV A (experimental) at SD Negeri 1 Metro Pusat in 2022/2023.